Alongside midwifery-led units: evidence and strategy and practice. (16th November 2010) - Walsh, D; Gribbin, C
Abstract : The choice of midwifery-led units (MLU's) is now enshrined in government policy on maternity services.1 In this abstract the authors discuss the variant of alongside MLU's which have existed in the United Kingdom since the late 1980s and internationally have been subjected to a number of randomised controlled trials. Hodnett et al 's (2005) original systematic review is currently being updated by one of us as part of a team.2 The evidence base is controversial because, although these facilities demonstrate more normal birth, a lowering of labour interventions and higher rates of satisfaction than conventional labour wards, there is also a non-significant trend to higher perinatal mortality. Both of us have experience of working within or alongside this model as a midwife or obstetrician and will present strengths and weaknesses of the model. Specifically the authors will discuss why there may be a possibility of higher perinatal deaths in this model and how to operationalise the model to reduce this likelihood. The authors will also discuss an alternative model. The systematic review itself speculates as to why this outcome might occur, suggesting poor inter-professional dynamics at the interface of transfer out of MLU to labour wards, an over-emphasis on normality within MLU philosophy and practice, underestimation of seriousness of the reason for transfer by labour ward staff, other unidentified factors or a chance occurrence. Each of these possible explanations will be examined and remedial measures, where appropriate, put forward to address them.